Desenvolvimento de sistemas de liberação prolongada de ácido rosmarínico para o tratamento de doenças oculares causadoras de neovascularização: obtenção e caracterização dos sistemas - Lorena Carla Vieira (2011)
The treatment of diseases of the posterior segment of the eye is limited once the conventional forms of drug administration fail to provide therapeutic levels drug to the vitreous, retina and choroids. Intravitreal injections have been used to deliver drugs to the posterior segment of the eye, but it is an invasive technique and shows risk of infections, retinal detachment and poor patient compliance. The biodegradable implants are able to release drugs directly to the vitreous and to maintain long-term vitreous concentration of drugs in therapeutic range. The poly (D,Llactidecoglycolide) (PLGA) is a biodegradable synthetic polymer widely used in drug delivery systems due to its biocompatibility and absence of significant toxicity accessed by in vivo studies. In this study, an intraocular implant based PLGA and rosmarinic acid, a polyphenol with promising antiangiogenic activity have been developed and characterized by DSC, FTIR and SEM, and its long-term in vitro release profile. The results sugest that it was possible to obtain biodegradable implants for RA release through reproducible methods that provide drug in dispersed and active form in the polymer matrix. The characterization techniques showed the absence of structural changes in RA and PLGA functional groups. The instability of RA in cell culture medium, prevented the use of biological assays for in vitro cytotoxicity and activity evaluation of the drug and the systems developed. The assessment of in vivo antiangiogenic activity of RA and biodegradable systems, by the chorioallantoic membrane assay, showed satisfactory results for future application of implants in the treatment of diseases that cause retinal neovascularization.